Comparison of Five PCR Methods for Detection of Helicobacter pylori DNA in Gastric Tissues - Lu, Jang-Jih (American Society for Microbiology, 1999)
Five different PCR methods for the detection of Helicobacter pylori were evaluated. The results of this study indicate that of the five PCR methods examined, the ureC (glmM) gene PCR is the most sensitive and specific for the detection of H. pylori in gastric biopsy specimens.